ANALISIS TINGKAT EFISIENSI EKONOMI DAN KESEJAHTERAAN USAHATANI KANGKUNG DARAT DAN AIR DI KECAMATAN TAMBAK KABUPATEN BANYUMAS - Ardilla Yughi, Sheila (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This research entitled â€œAnalysis of Economic Efficiency and Prosperity Level of Agribusiness Land and Water Kangkung in Tambak Subdistrict Banyumas Regencyâ€. The aim of this research are to analyze the economical eficiency comparison, total revenue, and prosperity level of kangkung farmers in Tambak Subdistrict, Banyumas Regency. This research uses a survey method. The results of this research: (1) for first hypotesis, show that land kangkung agribusiness is more eficient than water kangkung, (2) for the second hypotesis the result shows that land kangkung agribusiness is giving more profit than water kangkung agribusiness, (3) and result for the third hypothesis shows that land and water kangkung agribusiness have still not given prosperity to the farmers.